Accidental Death by Air Rifle A Case Report - Keten, Alper; Avşar, Abdullah; Karanfil, Ramazan; Okdemir, Erdem (The Bulletin of Legal Medicine, 2016)
Wounding potential and kinetic energy of airguns are less than firearms’. However, air guns may cause mortality and morbidity especially in children. They can cause fatal internal organ injuries from close range shots. Our case, a 6 year-old boy was injured by air rifle, the pellet entered the chest cavity and injured lung and aorta causing him to die as a result of bleeding. Studies showed some countries have limits on muzzle energy, ownership, utilization and manufacture of airguns contrary to Turkey. In this study, we discussed preventing injuries caused by air rifle through international practice and literature. Key words: Air rifle; death; autopsy